MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF JIGSAW KELAS IV SD MUHAMMADIYAH 1 LIMBOTO - Yulva S. Pongoliu; Yurni Rahman; Fandi H. Binggo (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
The purpose of this research is to improve student learning outcomes in the subject of Civic Education (PKN) through the Jigsaw Cooperative Learning Model in Grade IV of SD Muhammadiyah 1 Limboto. The type of research used is Classroom Action Research with the research subjects being 29 fourth-grade students of SD Muhammadiyah 1 Limboto. This study employed observation, tests, and documentation techniques. Data analysis techniques were also used. The results showed that the initial observation reached 17%, categorized as poor. In the first cycle, it increased to 52%, and in the second cycle, it improved to 86%, categorized as good. Based on these results, it can be concluded that the Jigsaw cooperative learning model can improve students’ learning outcomes in Civic Education in Grade IV of SD Muhammadiyah 1 Limboto, Gorontalo Regency.